Perancangan fasilitas stasiun berbasis kebutuhan dasar dan aktivitas penumpang kereta api jarak jauh: Studi kasus Stasiun Bandung - Saarah, Kamila Okta; Syarief, Achmad (Institut Seni Indonesia Yogyakarta, 2025)
Train travel is a popular mode of transportation in Indonesia, as proved by the increasing number of railway passengers in recent years. Railway stations serve as a crucial touchpoint for the passengers. Current studies on railway station facilities in Indonesia mostly evaluate the service quality and have yet to specifically address users’ basic needs and activities, and its influence on railway station design. This article discusses the findings of the basic needs and passengers’ activity mapping, utilising a mixed-method approach that integrates quantitative data obtained through passenger questionnaires (n=159) and qualitative data from observations and interviews (n=15). The results show that the priority basic needs of Indonesian intercity train passengers are: (1) safety, (2) reliability, (3) ease, (4) comfort, (5) cleanliness, and (6) responsiveness. These basic needs are then mapped onto the two main activity phases of intercity train passengers, namely: (1) departure phase: pre-boarding, boarding, and post-boarding, and (2) arrival phase: to continue the journey to the final destination. Identifying the basic needs and activities of intercity train passengers can provide a foundational framework for designing a railway station facility, thereby enhancing the overall passenger experience.